Legal Signs Fascinate Kevelson's Research on Semiotics - Broekman, Jan M. (SpringerBriefs in Law, 2018)
This engaging book examines the origins and first effects of the concept 'legal semiotics', focusing on the inventor of the term, Roberta Kevelson (1931-1998). It highlights the importance of her ideas and works which have contributed to legal theory, legal interpretation and philosophy of language. Kevelson's work is particularly relevant today, in our world of global electronic communication networks which rely so much on language, signs, signals and shortcuts. Kevelson could not have foreseen the 21st century, yet the story of her work and influence deserves more attention as it is key to our understanding of modern legal discourse and why law fascinates and is accepted in modern society. The authors draw on Kevelson's hitherto unknown Office Papers and Notes, and a biographical examination points to key influences in her work such as the early feminist movements of the US East Coast, the philosophy of Charles Sanders Peirce and the semiotics of Thomas Sebeok. This forms the basis for a more encompassing research of Kevelson's position, work and philosophical background, which the authors call for. A quick and enlightening read, this book interests a wide range of readers with an interest in legal history and the fields which Kevelson both drew on and influenced, including lawyers, students and scholars.